CLIP‐seq to Identify KSHV ORF57‐Binding RNA in Host B Cells. Issue 1 (6th May 2016) - Ma, Yanping; Liu, Poching; Majerciak, Vladimir; Zhu, Jun; Zheng, Zhi‐Ming
Abstract: Kaposi's sarcoma‐associated herpesvirus (KSHV), a human gamma ‐herpesvirus, is etiologically linked to the development of several malignancies, mainly Kaposi's sarcoma. Expressed as an early viral protein, KSHV ORF57 is essential for lytic replication and virion production. ORF57 selectively binds to a subset of viral RNA and affects nearly all aspects of viral RNA processing. To globally identify all viral and host RNA associated with KSHV ORF57 in the infected cells, we have utilized UV cross‐linking and immunoprecipitation (CLIP) of KSHV ORF57 combined with high‐throughput RNA sequencing (CLIP‐seq) to identify ORF57‐binding RNA in BCBL‐1 cells at genome‐wide level. This unit provides step‐by‐step details on this new method that is applicable for any pathogen or host RNA‐binding proteins by slight modification. © 2016 by John Wiley & Sons, Inc.